Blinatumomab induces autologous T-cell killing of chronic lymphocytic leukemia cells - Wong, Ryan (Ferrata Storti Foundation, 2013)
Chronic lymphocytic leukemia is an incurable B-cell malignancy that is associated with tumor cell-mediated T-cell dysfunction. It therefore represents a challenging disease for T-cell immunotherapeutics. The CD19/CD3 bi-specific antibody construct blinatumomab (AMG103 or MT103) has been tested clinically in non-Hodgkin’s lymphoma and acute lymphoblastic leukemia but has not been assessed in chronic lymphocytic leukemia. We investigated whether blinatumomab could overcome T-cell dysfunction in chronic lymphocytic leukemia in vitro. Blinatumomab was tested on peripheral blood mononuclear cells from 28 patients (treatment naïve and previously treated). T-cell activation and function, as well as cytotoxicity against leukemic tumor cells were measured. Blinatumomab induced T-cell activation, proliferation, cytokine secretion and granzyme B release in a manner similar to that occurring with stimulation with anti-CD3/anti-CD28 beads. However, only blinatumomab was able to induce tumor cell death and this was found to require blinatumomab-mediated conjugate formation between T cells and tumor cells. Cytotoxicity of tumor cells was observed at very low T-cell:tumor cell ratios. A three-dimensional model based on confocal microscopy suggested that up to 11 tumor cells could cluster round each T cell. Importantly, blinatumomab induced cytotoxicity against tumor cells in samples from both treatment-naïve and treated patients, and in the presence of co-culture pro-survival signals. The potent cytotoxic action of blinatumomab on tumor cells appears to involve conjugation of T cells with tumor cells at both the activation and effector stages. The efficacy of blinatumomab in vitro suggests that the bi-specific antibody approach may be a powerful immunotherapeutic strategy in chronic lymphocytic leukemia.